2021
DOI: 10.1111/dech.12638
|View full text |Cite
|
Sign up to set email alerts
|

Where Can the Crow Make Friends? Sci‐Hub's Activities in the Library of Development Studies and its Implications for the Field

Abstract: This study examines data on the worldwide use of the shadow library website Sci-Hub. It focuses particularly on the discipline of development studies, taking a critical look at current practices in scientific publishing and their implications for scientific conduct in this field. In the context of discussions about open science, the data demonstrate that Sci-Hub represents an existing network of open access literature. The study first describes the extent and geographic distribution of download requests from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Our data also showed that academics from low-income countries employ scholarly piracy services more frequently. This finding allows us to generalize this trend, which has already been analyzed in some disciplines (Sagemüller et al, 2021). We understand that academics from universities and institutions with lower economic resources are keener to solve the lack of funding and gaps in their libraries by turning to Sci-Hub and other Black OA alternatives.…”
Section: Discussionsupporting
confidence: 58%
“…Our data also showed that academics from low-income countries employ scholarly piracy services more frequently. This finding allows us to generalize this trend, which has already been analyzed in some disciplines (Sagemüller et al, 2021). We understand that academics from universities and institutions with lower economic resources are keener to solve the lack of funding and gaps in their libraries by turning to Sci-Hub and other Black OA alternatives.…”
Section: Discussionsupporting
confidence: 58%
“…It's still not known how sci-hub gets credentials, although there is a lot of speculation, whether it is from donations or cyberattacks (Himmelstein et al, 2018;Sagemüller et al, 2021), it already gathers a large collection of paywalled scholarly research (Björk, 2017;Greshake, 2017). In the literature, this type of access, provided by the shadow libraries, is often referred to as «black open access» or «guerrilla open access» (Björk, 2017).…”
Section: Illegal Access To Scholarly Researchmentioning
confidence: 99%
“…Therefore, besides not guaranteeing that the contents that are being accessed are the true sources, since it isn't authoritative, it doesn't warrant the quality and long-term preservation, besides not talking of compatibility with standards and interoperability with other structures of scholarly communication, something of which a proper infrastructure should assure. So, sci-hub isn't committed to opening up research, since it fails to address key attributes of open science (Sagemüller et al, 2021).…”
Section: Sci-hub and Academic Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent example is Sci‐Hub, which provides free access to publications behind paywalls through the fraudulent use of existing licensee accounts. The use of Sci‐Hub within the academic community (Bohannon, 2016; Greshake, 2016), the finding that two‐thirds of downloads in the field of medical research stem from low‐and lower‐middle‐income countries (Sagemüller et al, 2021; Till et al, 2019), and its widespread use and global availability allow tentative answers to what‐if questions relating to the free‐of‐charge provision of academic knowledge as a public good: To what extent can free access alone contribute toward a leveling of the playing field? Does an increase in access allow more or other scientists, or even institutions, to participate in cutting‐edge discussions?…”
Section: Introductionmentioning
confidence: 99%